ANALISIS PERHITUNGAN TARIF BIAYA PENYELENGGARAAN PENDIDIKAN DAN IMPLIKASINYA TERHADAP PENDAPATAN SPP SEKOLAH - Widarsono, Agus; Zulfikar, Faris (Jurnal Riset Akuntansi dan Keuangan, 2013)
School is one form of educational services business which was originally only a social institution, but currently a business institution that participate in seeking profit. With the various tuition fees in school, the determination of tuition fees should be accurate because of the effect on school revenues. So it takes a method of tariff determination that can overcome the problem, namely Activity Costing System.The purpose of this research is to know the determination of tariff of education cost using Activitty Costing System method, difference between tariff cost determination of education using traditional method and ACS method, to know the effect of costing tariff determination using traditional method to school fee income and to know the effect of determination Tariff of educational cost using ACS method to school fee income.This study uses sample data on the calculation of unit cost of new school year education services, and the costs that became the basis of tariff determination in 2010 to determine the tariff of SPP in 2011. Hypothesis testing of this study was conducted by using two sample t-test, coefficient Correlation and coefficient of determination.Result of research indicate that tariff determination using traditional method and ACS seen some difference difference between two tariff, but if used statistical approach hence both tariff have no significant difference. Based on the value of the correlation coefficient between the influence of the tariff of the traditional method SPP with the income of school fees obtained by 0.884 with a positive direction and coefisein determination sebsear 78.2%. Based on the value of the correlation coefficient between the influence of the tariff rate of SPP ACS method with the income of school fees obtained by 0.873 with a positive direction and coefisein determination sebsear 76.2%. With these results both tariffs equally affect the income SPP